1997
DOI: 10.1183/09031936.97.10051079
|View full text |Cite
|
Sign up to set email alerts
|

Disabling dyspnoea in patients with advanced disease: lack of effect of nebulized morphine

Abstract: The purpose of this placebo-controlled, double-blind, randomized study was to assess the effect of nebulized morphine on dyspnoea perceived at rest by patients with advanced disease.Seventeen hospital in-patients with disabling dyspnoea received isotonic saline or morphine via nebulization for 10 min through a mouthpiece, combined with oxygen via nasal prongs. On four consecutive days, they were given one of the four following treatments in random order: saline with 2 L·min -1 oxygen; 10 mg morphine with 2 L·m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 21 publications
0
37
1
3
Order By: Relevance
“…A review of 18 randomized studies comparing aerosolized and intravenous narcotics demonstrated comparable effectiveness, with neither superior. 113 This is in contrast to a randomized crossover study by Noseda et al 114 showing that neither 10 nor 20 mg of nebulized morphine was any different than a saline placebo as judged by patient dyspnea scales. A similar study using 20 and 40 mg of nebulized morphine produced no improvement in perceived dyspnea or the 6-min walk test relative to placebo.…”
Section: Aerosolized Analgesics Opioidscontrasting
confidence: 46%
“…A review of 18 randomized studies comparing aerosolized and intravenous narcotics demonstrated comparable effectiveness, with neither superior. 113 This is in contrast to a randomized crossover study by Noseda et al 114 showing that neither 10 nor 20 mg of nebulized morphine was any different than a saline placebo as judged by patient dyspnea scales. A similar study using 20 and 40 mg of nebulized morphine produced no improvement in perceived dyspnea or the 6-min walk test relative to placebo.…”
Section: Aerosolized Analgesics Opioidscontrasting
confidence: 46%
“…Fifteen of those trials [4,7,10,11,15,17,21,23,28,30,32,36,39,47] were also eligible for our systematic review. The literature sources, abbreviated search strategy, and selection criteria were provided.…”
Section: Resultsmentioning
confidence: 99%
“…Only five trials reported using a washout period [14,24,31,39,40]. Five trials reported a calculated sample size [2,8,32,36,39], and three met the target [32,36,39]. Two trials received support from pharmaceutical companies [1,46].…”
Section: Randomized and Nonrandomized Trialsmentioning
confidence: 96%
See 1 more Smart Citation
“…Studien zur Morphiumtherapie bei Patienten mit chronisch obstruktiver Lungenerkrankung (COPD) und Lungenemphysem ergaben ein kontroverses Bild. Neben nachgewiesener Effektivität [7,9,10,17,21,23] blieben andere Studien ohne Effektivitätsnachweis [1,4,6,8,[10][11][12]16].…”
unclassified